Analisis Fungsi Ruang Terbuka Sebagai Sarana Penunjang Aktivitas Akademik dan Sosial Bagi Mahasiswa di Lingkungan Kampus Politeknik Negeri Bandung (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2025)
Open spaces within a campus serve as vital public areas that support the development of students’ academic knowledge, creativity, and soft skills through environmental interaction. The availability, design, and quality of campus open spaces play a crucial role in shaping a liveable and engaging academic environment. At Bandung State Polytechnic (Polban), open space utilization remains passive due to the limited facilities in various areas, resulting in low student engagement. This study aims to examine the existing conditions and analyze the potential of open spaces within the Polban campus based on academic open space (AOS) typologies, focusing on their function in supporting academic and social activities. A qualitative approach was employed, with primary data collected through field observations, document analysis, and interviews. The findings reveal that several areas meet the criteria to function as passive spaces and small gathering areas, supporting academic-related activities. Additionally, from a social perspective, the campus possesses potential areas for outdoor dining, large gathering spaces, and symbolic spaces. The study emphasizes the importance of aligning open space design with student activity needs and enhancing the available facilities to optimize usage. The results can serve as a reference for future campus open space planning and development that is more responsive to student needs and campus life dynamics.